Comparative Effectiveness and Safety of Direct Oral Anticoagulants Versus Warfarin Among Adults With Cancer and Atrial Fibrillation. Issue 12 (1st December 2022) - Mehta, Hemalkumar B.; An, Huijun; Ardeshirrouhanifard, Shirin; Raji, Mukaila A.; Alexander, G. Caleb; Segal, Jodi B.
Abstract : Background: While clinical guidelines recommend direct-acting oral anticoagulants (DOAC) over warfarin to treat isolated nonvalvular atrial fibrillation, guidelines are silent regarding nonvalvular atrial fibrillation treatment among individuals with cancer, reflecting the paucity of evidence in this setting. We quantified relative risk of ischemic stroke or systemic embolism and major bleeding (primary outcomes), and all-cause and cardiovascular death (secondary outcomes) among older individuals with cancer and nonvalvular atrial fibrillation comparing DOACs and warfarin. Methods: This retrospective cohort study used Surveillance, Epidemiology, and End Results cancer registry and linked US Medicare data from 2010 through 2016, and included individuals diagnosed with cancer and nonvalvular atrial fibrillation who newly initiated DOAC or warfarin. We used inverse probability of treatment weighting to control confounding. We used competing risk regression for primary outcomes and cardiovascular death, and Cox proportional hazard regression for all-cause death. Results: Among 7675 individuals included in the cohort, 4244 (55.3%) received DOACs and 3431 (44.7%) warfarin. In the inverse probability of treatment weighting analysis, there was no statistically significant difference among DOAC and warfarin users in the risk of ischemic stroke or systemic embolism (1.24 versus 1.19 events per 100 person-years, adjusted hazard ratio 1.41 [95% CI, 0.92–2.14]), major bleeding (3.08 versus 4.49 events per 100 person-years, adjusted hazard ratio 0.90 [95% CI, 0.70–1.17]), and cardiovascular death (1.88 versus 3.14 per 100 person-years, adjusted hazard ratio 0.82 [95% CI, 0.59–0.1.13]). DOAC users had significantly lower risk of all-cause death (7.09 versus 13.3 per 100 person-years, adjusted hazard ratio 0.81 [95% CI, 0.69–0.94]) compared to warfarin users. Conclusions: Older adults with cancer and atrial fibrillation exposed to DOACs had similar risks of stroke and systemic embolism and major bleeding as those exposed to warfarin. Relative to warfarin, DOAC use was associated with a similar risk of cardiovascular death and a lower risk of all-cause death.